Frequency of thiopurine S-methyltransferase gene variations in Turkish children with acute leukemia - Akın, Dilara Fatma; Aşlar-Öner, Deniz; Kürekçi, Emin; Akar, Nejat (The Turkish Journal of Pediatrics, 2018)
In this study we aim to determine the genotype distribution and allele frequencies of common TPMT (*2, *3A, *3B and *3C) polymorphisms in Turkish children with acute leukemia. The study population consisted of 169 patients aged between 1 and 15 years who were admitted to Losante Pediatric Hematology and Children`s Hospital with the diagnosis of acute leukemia. Genotyping of TPMT polymorphisms was screened with real-time PCR using fluorescence melting curve detection analysis. We found that the frequencies of four allelic variants of TPMT are *2 (238 G > C) (0,0%), *3A (460G > A and 719A > G) (1.7%), *3B (460G > A) (1,7%) and *3C (719A > G) (2.4%). Frequency of TPMT alleles increases the efficacy of leukemia treatment. Thus, TPMT genotyping can be useful for optimizing 6-MP therapy.
Keywords: TPMT; childhood; leukemia; polymorphism